Prevalence and Risk Factors of Hepatitis A, B and C in Neelum Valley District of Azad Kashmir, Pakistan - Akhtar, Tasleem; Kazmi, Syed Ayaz; Abdul Rauf; Shahid, Beenish; Roop Riaz; Latif, Muhammad Zahid; Sundus Khawaja; Hassan Abdullah; Iqra Batool; Salma Farooq; Anjum, Zeeshan (Indus Journal of Bioscience Research, 2025)
Background: No prior studies have assessed hepatitis A, B, and C prevalence in Neelum Valley, Azad Kashmir, a major tourist hub along the Line of Control. This study evaluates the prevalence and risk factors associated with these infections in the region. Methods: A total of 374 participants (286 males, 88 females) from Neelum Valley were surveyed, and serum samples were tested for hepatitis markers using immuno-chromatographic tests and Real-Time PCR. Liver function markers (ALT, ALP, and Bilirubin) were also analyzed. Statistical analysis was conducted using GraphPad Prism V. 7.04. Results: The prevalence of recent hepatitis A infection (HAV IgM Positive) was 0.8%, while 4.8% had prior exposure (HAV IgG Positive). Hepatitis B (HBsAg positivity) was detected in 2.4%, with 1.3% showing active viral replication (HBV DNA Positive). Hepatitis C exposure (anti-HCV positivity) was 1.3%, with 0.5% showing active infection (HCV RNA Positive). All participants had normal liver function markers. Younger individuals (18–25 years) had higher infection rates, and males showed a greater prevalence than females for all infections. Significant risk factors (p < 0.0001) included contaminated food or water, jaundice history, hospitalization, blood transfusions, ear/nose piercing, tattooing, and treatment from local practitioners. Conclusions: The prevalence of hepatitis A, B, and C in Neelum Valley is lower than in some regional studies but remains a public health concern. The influx of tourists may facilitate disease transmission, highlighting the need for improved sanitation and healthcare measures.